2013
DOI: 10.1055/s-0032-1328173
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Activity of the Natural Compound (+)-Limonene Epoxide against Schistosoma mansoni

Abstract: Blood fluke of the genus Schistosoma are the etiological agents of human schistosomiasis, an important neglected tropical disease that afflicts over 200 million people worldwide. The treatment for this disease relies heavily on a single drug, praziquantel. Recent reports of praziquantel resistance raise concerns about future control of the disease and show the importance of developing new antischistosomal drugs. Currently, natural products have been a good source for drug development. (+)-Limonene epoxide is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 37 publications
(60 reference statements)
8
31
0
Order By: Relevance
“…In this context, alterations of the tegument of S. mansoni induced by several antischistosomal compounds have also been described (25)(26)(27)(28)(29). In this study, we observed extensive tegumental damage in S. mansoni that intensified progressively when the concentrations of the oxindolimine-metal complexes tested increased.…”
supporting
confidence: 69%
“…In this context, alterations of the tegument of S. mansoni induced by several antischistosomal compounds have also been described (25)(26)(27)(28)(29). In this study, we observed extensive tegumental damage in S. mansoni that intensified progressively when the concentrations of the oxindolimine-metal complexes tested increased.…”
supporting
confidence: 69%
“…The mechanism by which terpenes exert their schistosomicidal effect may be that, due to inherent lipophilicity, some terpenes will easily cross plasmatic membranes and, consequently, may also interact with intracellular molecules of parasites. In fact, some of the compounds described herein are capable of causing morphological changes in the integument of worms, and a relationship has been observed between tegumental damage and the death of worms [39,56,[59][60].…”
Section: Terpenesmentioning
confidence: 83%
“…The terpenes with antischistosomal activity are: rotundifolone [66], (+)-limonene epoxide [56], and carvacryl acetate, a derivative of carvacrol (monoterpenes) [39]; artemisinin and its derivatives [30,31], nerolidol [59], and budlein-A and its derivatives [38] (sesquiterpenes); phytol [60] (diterpene), betulin [37] and its triphenylphosphonium derivatives [69], balsaminol F, karavilagenin C [36] (triterpenes) (Figure 1). Importantly, among the group of terpenes, in vitro and in vivo antischistosomal properties have been described only for artemisinin and its derivatives, phytol and triphenylphosphonium derivatives, whereas it was reported in vitro schitosomicidal activity for other terpenes (Table 1).…”
Section: Terpenesmentioning
confidence: 99%
“…Acetate carvacrol (6.25 µg/mL) affected motility, parasite tegument and oviposition [7]. Similar results were also found for phloroglucinol derivatives (aspidina, flavaspidico acid, methylenebis-aspidinol and desaspidina) [21], dermaseptina antimicrobial peptide [27], essential oils of Piper cubeba and Tagete serecta [21,28], (+)-Epoxy-Limonene [29] and Mitracarpus frigidus methanolic extract [30].…”
Section: Discussionmentioning
confidence: 53%